HUMAN RESOURCE MANAGEMENT EVALUATION IN IMPROVING EMPLOYEE JOB SATISFACTION IN THE MANUFACTURING INDUSTRY IN BEKASI CITY - Sumarsid, Sumarsid (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study aims to evaluate human resource (HR) management in improving employee job satisfaction in the manufacturing industry in Bekasi City. A qualitative approach was used with data collection through in-depth interviews, observations, and document analysis. The results showed that factors such as training and development, compensation systems, work environment, and leadership style significantly create job satisfaction. It has been demonstrated that skills can be enhanced through training tailored to the job's specific requirements. Additionally, employees' well-being is significantly influenced by adequate compensation, which includes supplementary benefits. Job satisfaction is also positively influenced by a transformational leadership style and a conducive work environment. Nevertheless, this investigation identified obstacles, including inadequate communication, budgetary allocations for HR development initiatives, and employee participation in decision-making processes. This study recommends that companies formulate more flexible HR management strategies centred on employee needs to enhance job satisfaction and overall productivity.